2002
DOI: 10.1002/jsfa.1268
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of maturity stages, including quality and aroma, in ‘Royal Glory’ peaches and ‘Big Top’ nectarines

Abstract: Ethylene production, quality attributes and aroma compounds were analysed to determine the maturity evolution of 'Big Top' nectarines and 'Royal Glory' peaches at harvest dates ranging from 89 to 116 days after full bloom (DAFB) for nectarines and from 85 to 112 DAFB for peaches. These cultivars are highly coloured even in the early stages of maturity. However, the two cultivars had different patterns of ethylene production, this being slower in nectarines than in peaches. Principal component analysis (PCA) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 17 publications
5
36
0
2
Order By: Relevance
“…36 -38 However, it is not known what specific ethylene value is needed to trigger the ripening process in this variety of peach, since each variety is different. 35 Our results indicated an advance in the climacteric peak for RDI treatments, and this was associated with fruit softening after cold storage. Both processes are compatible with the idea of an advance in fruit ripening for RDI-SII peaches.…”
Section: Ethylene Production and Respirationmentioning
confidence: 66%
See 1 more Smart Citation
“…36 -38 However, it is not known what specific ethylene value is needed to trigger the ripening process in this variety of peach, since each variety is different. 35 Our results indicated an advance in the climacteric peak for RDI treatments, and this was associated with fruit softening after cold storage. Both processes are compatible with the idea of an advance in fruit ripening for RDI-SII peaches.…”
Section: Ethylene Production and Respirationmentioning
confidence: 66%
“…In the end, fruits from RDI-SII and RDI-SII-PH appeared to ripen normally, whereas Control fruits seemed to ripen with difficulty ( Fig 6C). 35 SSC was higher for RDI-SII in the three samples, and it was not possible to attribute an advance of maturity in RDI-SII based only on this parameter. Differences in fruit quality between irrigation treatments tended to be more evident after 1 week of cold storage.…”
Section: Ethylene Production and Respirationmentioning
confidence: 99%
“…PCA has been previously used to establish genetic relationships among cultivars and to study correlations among fruit traits within peach (Brovelli et al 1999;Lavilla et al 2002;Crisosto et al 2006a) and apricot genotypes (Badenes et al 1998;Gurrieri et al 2001;Ruiz and Egea 2008). The PCA carried out in this work showed that more than eighty per cent of the observed variance could be explained by the first five components.…”
Section: Principal Component Analysis and Grouping Of Progeniesmentioning
confidence: 79%
“…Table 6 summarizes the content of organic acids in the samples analyzed. The values are within the range of values previously describes in the literature, but obviously depend on the origin, cultivar, harvest date and degree of maturation (Flores, Hellín, & Fenoll, 2012;Lavilla, Recasens, Lopez, & Puy, 2002;Wu, Quilot, Génard, Kervella, & Li, 2005). Malic acid followed by citric acid were the major organic acids of peach fruit among all organic acids analyzed representing more than 80% of the total acid content analyzed.…”
Section: Analysis Of Peach Extractsmentioning
confidence: 97%